MENEMUKAN HARMONI BATIN MELALUI ZUHUD: TINJAUAN LITERATUR TERHADAP KONSEP WELL-BEING - Selma Febrianti; Nasywa Amelia Dewi (CV. Denasya Smart Publisher, 2025)
This research examines the relationship between zuhud and psychological well-being can provide broader insights. The phenomenon of zuhud is not only of theoretical value in the study of Sufism, but also has practical significance in shaping human morals. On the other hand, psychological well-being is a condition where individuals feel happy, peaceful, have a purpose in life, and are able to live life positively. So it is important to examine the relationship between zuhud and psychological well-being so that we can understand how spiritual teachings can support mental health amid the challenges of modern life. This study used a qualitative research method with a literature review for the research process. The results of this study concluded that Zuhud is an attitude that releases dependence from the worldly and prioritizes spirituality in the hereafter, by applying zuhud plays a very positive role in shaping inner calm, self-control, and can be grateful at all times. .